Analisis Nilai-Nilai Islam Berkemajuan dalam Buku Ajar Kemuhammadiyahan Tingkat SMP/MTs - Muhammad Adz Dzahabie; Riza Ashfari Mizan; Zaenudin Mudaham Amin; Heri Rifhan Halili (Education Reserach Center, 2026)
In this era of disruption and globalisation, Islamic education is required not only to teach normative teachings, but also to instil progressive values that are relevant to the times. Muhammadiyah, as a modernist Islamic movement, offers the concept of ‘Islam Berkemajuan’ (Progressive Islam), which encompasses the values of rationality, renewal, social justice, and openness to science. The Kemuhammadiyahan textbook at the junior high school/MTs level is a strategic instrument in transmitting these values to the younger generation. This study aims to analyse the representation of Progressive Islam values in Muhammadiyah textbooks used in Muhammadiyah educational institutions. Using a qualitative approach and a contextual hermeneutic content analysis method, this study examines how values such as tajdid, social tauhid, enlightenment, and tolerance are represented in narratives and learning materials. The results show that the textbooks generally contain Progressive Islam values, especially in terms of intellectual renewal, social commitment, and the integration of faith and knowledge. However, some aspects, such as ecological awareness and the digitalisation of Islamic values, still receive little attention. These findings recommend strengthening a more comprehensive and contextual Progressive Islam-based curriculum.